Morphological and multi-gene phylogenetic analyses reveal five new hyphomycetes from freshwater habitats - Zhang, Ya-Zhou; Chen, Qi-Lei; Ma, Jian; Lu, Yong-Zhong; Chen, Hu-Biao; Liu, Ning-Guo (Frontiers in Microbiology, 2023)
During the survey on freshwater hyphomycetes in Guangxi, Guizhou and Hainan Provinces, China, five fresh collections were encountered. Based on their morphology, these five isolates were identified as belonging to Hermatomyces, Kirschsteiniothelia, Paramonodictys, Pleopunctum and Sparticola. Multi-gene phylogenetic analyses were performed for each genus, which resulted in the identification of five new species, namely Hermatomyces hainanensis, Kirschsteiniothelia ramus, Paramonodictys globosa, Pleopunctum guizhouense and Sparticola irregularis. Detailed descriptions and illustrations of the morphological characteristics of these new taxa were provided. This research enriches the biodiversity of freshwater dematiaceous hyphomycetes.